Fast sweep-rate plastic Faraday force magnetometer with simultaneous sample temperature measurement - Slobinsky, Demian Gustavo (2012)
We present a design for a magnetometer capable of operating at temperatures down to 50 mK and magnetic fields up to 15 T with integrated sample temperature measurement. Our design is based on the concept of a Faraday force magnetometer with a load-sensing variable capacitor. A plastic body allows for fast sweep rates and sample temperature measurement, and the possibility of regulating the initial capacitance simplifies the initial bridge balancing. Under moderate gradient fields of ∼1 T/m our prototype performed with a resolution better than 1 × 10−5 emu. The magnetometer can be operated either in a dc mode, or in an oscillatory mode which allows the determination of the magnetic susceptibility. We present measurements on Dy2Ti2O7 and Sr3Ru2O7 as an example of its performance.